Design and simulation of lab-on-chip - Shahnawaz Pukkeyil Shamsuddin. (2011)
About 3.4 million water-related deaths involving microbial pathogens are reported around the world. Natural disasters like tsunami and floods further promote the outbreak of water born diseases. Conventional methods to detect pathogens or micro organisms in water require few hours to do process. The water industry requires a fast and effective Cryptosporidium pathogen detection system, which will save peoples life around the world this gives the motivation for this project to engineer a rapid microbial detection system. Microfluidics has become a great tool in analysis of cells and particles. It has the ability to precisely control the flow rate through narrow channels so that microbes can be detected individually. High speed detection requires high flow rate in microfluidic system, this has always been a problem because of the high pressure experienced in the system. This project talks about design considerations and fabrication process of high flow rate microfluidic chip using two widely used materials in micro fabrication PDMS and glass. The target flow rate for microbe detection was set to be 10l/hr, experiment conducted shows that a flow rate was achieved. The report also talks about the integration of macro system to micro system to have a leak free flow of water in system.